Serum myeloperoxidase levels are associated with the future risk of coronary artery disease in apparently healthy individuals : The EPIC-Norfolk prospective population study - MEUWESE, Marijn C; STROES, Erik S. G; MATTHIJS BOEKHOLDT, S; HAZEN, Stanley L; VAN MIERT, Joram N; KUIVENHOVEN, Jan Albert; SCHAUB, Robert G; WAREHAM, Nicholas J; LUBEN, Robert; KASTELEIN, John J. P; KHAW, Kay-Tee (Journal of the American College of Cardiology, 2007)
We evaluated whether serum myeloperoxidase (MPO) levels are associated with the risk of future development of coronary artery disease (CAD) in apparently healthy individuals. An enzyme of the innate immune system, MPO exhibits a wide array of proatherogenic effects. These include induction of oxidative damage to low-density lipoprotein (LDL) and high-density lipoprotein (HDL) cholesterol and promotion of plaque vulnerability. Recent studies revealed that MPO independently predicts adverse outcomes in patients with chest pain or suspected acute coronary syndrome. Myeloperoxidase was measured in baseline samples of a case-control study nested in the prospective EPIC (European Prospective Investigation into Cancer and Nutrition)-Norfolk population study. Case subjects (n = 1,138) were apparently healthy men and women who developed CAD during 8-year follow-up. Control subjects (n = 2,237), matched for age, gender, and enrollment time, remained free of CAD. The MPO levels were significantly higher in case subjects than in control subjects and correlated with C-reactive protein (CRP) (rho = 0.25; p < 0.001) and white blood cell count (rho = 0.33; p < 0.001). Risk of future CAD increased in consecutive quartiles of MPO concentration, with an odds ratio (OR) of 1.49 in the top versus bottom quartile (95% confidence interval [CI] 1.20 to 1.84; p < 0.001). After adjustment for traditional risk factors, the OR in the top quartile remained significant at 1.36 (95% CI 1.07 to 1.73). Elevated MPO levels (>728 pmol/l) similarly predicted increased risk of future CAD among participants with either LDL-cholesterol <130 mg/dl, HDL-cholesterol >50 mg/dl, or CRP <2.0 mg/l (OR 1.52 [95% CI 1.21 to 1.91], 1.59 [95% CI 1.24 to 2.05], and 1.42 [95% CI 1.14 to 1.77)], respectively). Elevated MPO levels predict future risk of CAD in apparently healthy individuals. This study suggests that inflammatory activation precedes the onset of overt CAD by many years.